AB0571 Efficacy of tocilizumab prescribed as first line biologic: A 48-week post marketing observational study in romanian rheumatoid arthritis patients (stone) - interim analysis. (23rd January 2014) - Ionescu, R.; Codreanu, C.; Ancuta, I.; Balanescu, A.; Parvu, M.; Opris, D.
Abstract : Background: Optimal care of patients with Rheumatoid Arthritis (RA) requires an integrated approach of pharmacologic therapies which usually includes conventional DMARD's and biological DMARD's such as Tocilizumab (TCZ). In Romania, official guidelines recommend start of a biologic compound only after failure of 2 consecutive cDMARD's administered at a maximum tolerated dose (MTX is mandatory). TCZ is used as first line biological therapy according to SPC and local therapeutic guidelines approved by Romanian Ministry of Health. Objectives: The purpose of this interim analysis is to evaluate the efficacy of TCZ therapy in patients with RA who have had intolerance or inadequate response prior to cDMARD's therapies in Romania. Methods: In this open-label, multicenter, prospective, non-comparative, non-interventional study, target population was represented by adult patients with active RA, DMARD-IR and biologics naïve, administrated according to real life practice. They were treated for 48 weeks with TCZ, prescribed according to the current Romanian standard of care (8 mg/kg every 4 weeks). The primary objective was the median change in DAS28 at W24 and 48. Secondary objectives included: remission (DAS28 <2.6), low disease activity rates and EULAR response rates. We analyzed 62 patients (87.1% women, 12.9% men, average age of 50) who reached W48 of treatment at 1st September 2011. Results: At baseline, median DAS28 was 6.66, with 91.84% of patients in HDA and 8.06% in MDA. At W24, DAS28 decreased to 2.59, with 51.61% of patients achieving remission and 22.58% in LDA. At W48, DAS28 was 2.30 and 60.38% patients reached remission and only 16.98% were in LDA. For analyzed patients median change in DAS28 was - 4.07 at W24. This response is consolidated by results obtained at W48 (ΔDAS28=4.36). Conclusions: In our study, significantly improved DAS remission rates were achieved suggesting that Tocilizumab therapy can be successful used, in real life settings, in order to meet Treat-to-Target principles, for patients with active RA, DMARD-IR and Biologics naive. Disclosure of Interest: None Declared